Platelet-Specific Deletion of Cyclooxygenase-1 Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice - Sacco, Angela; Bruno, Annalisa; Contursi, Annalisa; Dovizio, Melania; Tacconelli, Stefania; Ricciotti, Emanuela; Guillem-Llobat, Paloma; Salvatore, Tania; Di Francesco, Luigia; Fullone, Rosa; Ballerini, Patrizia; Arena, Vincenzo; et al. (The Journal of pharmacology and experimental therapeutics, 2019)
Inflammatory bowel disease (IBD) is associated with an increased risk for thromboembolism, platelet activation, and abnormalities in platelet number and size. In colitis, platelets can extravasate into the colonic interstitium. We generated a mouse with a specific deletion of cyclooxygenase (COX)-1 in megakaryocytes/platelets [(COX-1 conditional knockout (cKO)] to clarify the role of platelet activation in the development of inflammation and fibrosis in dextran sodium sulfate (DSS)-induced colitis. The disease activity index was assessed, and colonic specimens were evaluated for histologic features of epithelial barrier damage, inflammation, and fibrosis. Cocultures of platelets and myofibroblasts were performed. We found that the specific deletion of COX-1 in platelets, which recapitulated the human pharmacodynamics of low-dose aspirin, that is, suppression of platelet thromboxane (TX)A production associated with substantial sparing of the systemic production of prostacyclin, resulted in milder symptoms of colitis, in the acute phase, and almost complete recovery from the disease after DSS withdrawal. Reduced colonic accumulation of macrophages and myofibroblasts and collagen deposition was found. Platelet-derived TXA enhanced the ability of myofibroblasts to proliferate and migrate in vitro, and these effects were prevented by platelet COX-1 inhibition or antagonism of the TXA receptor. Our findings allow a significant advance in the knowledge of the role of platelet-derived TXA in the development of colitis and fibrosis in response to intestinal damage and provide the rationale to investigate the potential efficacy of the antiplatelet agent low-dose aspirin in limiting the inflammatory response and fibrosis associated with IBD. SIGNIFICANCE STATEMENT: Inflammatory bowel disease (IBD) is characterized by the development of a chronic inflammatory response, which can lead to intestinal fibrosis for which currently there is no medical treatment. Through the generation of a mouse with specific deletion of cyclooxygenase-1 in megakaryocytes/platelets, which recapitulates the human pharmacodynamics of low-dose aspirin, we demonstrate the important role of platelet-derived thromboxane A in the development of experimental colitis and fibrosis, thus providing the rationale to investigate the potential efficacy of low-dose aspirin in limiting the inflammation and tissue damage associated with IBD.